Reference Values of Nerve Cross-sectional Area Obtained by Ultrasound in the Upper Extremity Correlated with Electrodiagnosis in Thai Adults - Ngernprasertsiri, Siriwadee; Puprasert, Chapa; Wimonwattrawatee, Pariya (Biomedical Sciences and Clinical Medicine, 2023)
OBJECTIVE To evaluate the ultrasonography cross-sectional area (CSA) reference values of nerves in the upper extremity correlated with electrodiagnosis in healthy Thai adults. METHODS A cross-sectional study was performed. Ninety participants were recruited and their CSA at 10 sites on the median, ulnar, and radial nerves were measured bilaterally. A nerve conduction study (NCS) was conducted and the correlations between the nerve CSA and age, sex, height, weight, body mass index (BMI), and NCS parameters were studied. RESULTS The mean CSA ranged from 5.8±1.4 to 9.5±1.5 mm2 along the median nerve and 4.5±0.8 to 7.7±1.7 mm2 along the ulnar nerve. The mean CSAs of the radial nerve at the elbow and spiral groove were 5.0±0.9 and 4.6±0.8 mm2, respectively. The CSA of the median nerve at the wrist and the CSA of the radial nerve at the spiral groove were positively correlated with weight and BMI, whereas the CSA of the median nerve at the elbow was positively correlated only with weight. There was an association between CSA values and electrodiagnosis parameters as the nerve CSA increased, as the latency was prolonged, and as the amplitude decreased. CONCLUSIONS The reference values of nerve CSA in the upper extremity at multiple sites can be helpful in the evaluation of peripheral nerve disorders in the Thai population.